A Study of Respiratory System Related Causes of Sudden Death (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Sudden death due to respiratory illness is one of the leading causes of sudden and natural deaths all over the world, the frequency is, however, more in developing and underdeveloped countries. A retrospective study was conducted at our centre in Kasturba Medical College, Mangalore, in cases which came with the history of sudden death with the aim to study respiratory system-related causes of sudden death. The cases with gross positive findings in lungs were taken as samples for study. Out of 2,515 autopsies conducted during the study period, 274 (10.89%) were of sudden death, of which 81 (29.56%) were due to respiratory system-related diseases. Respiratory causes of deaths were seen mostly in the age group of 40–49years (25.9%) and those above 60 years of age (25.9%). Male comprised 88.88% of death related to respiratory causes. Various forms of respiratory illness causing death were pulmonary tuberculosis (TB, 43.2%), pneumonia (28.39%) pulmonary TB with pneumonia (4.93%) and upper respiratory tract diseases association with other extra-pulmonary causes (23.45%). This study emphasizes need to create awareness among people about respiratory health and regular medical checkup.
Keywords: Sudden death; Respiratory system; Indian population; Pulmonary TB; Upper respiratory tract diseases